Refugees are (not) welcome here the paradox of protection in Canada - Masoumi, Azar (Law and society series, 2023)
"State-controlled refugee protection in Canada has gone through paradoxical developments in recent decades; while refugee rights have expanded, access to these rights has tightened. Previously unrecognized groups – such as women experiencing gender-based violence and 2SLGBTQ+ populations – are now considered legitimate refugees in refugee-law practices. Simultaneously, increasingly stringent administrative measures have made it harder for refugees to secure refugee status. Refugees Are (Not) Welcome Here draws on archival and media sources, interviews, and organizational data to examine how refugee claims are administered within a complex, contradictory regime that maintains its own legal and bureaucratic silos. Azar Masoumi explains why state-controlled refugee protection persists despite its many failures, not just in Canada but globally."